ROS MEDIATED THERANOSTIC MATERIALS - Abilova, Ayaulym (School of Engineering and Digital Sciences, 2023)
Image-guided therapy or theranostics is a promising emerging approach in drug delivery systems that allows for overcoming severe side effects of conventional treatment options. Reactive oxygen species (ROS) are essential players in normal cell functioning; however, their abnormal metabolism is associated with numerous acute and chronic conditions. Therefore, the overproduction of ROS may serve as an attractive biomarker for tracking the early progression of the diseases. Herein, we studied ROS activatable nanoparticles comprising peroxyoxalate esters capable of multimodal imaging and smart drug release, simultaneously, in the biomarker-rich microenvironment. A fluorinated oxalate compound (FOC), chemiexcitation source, fluorophore, or photosensitizer were co-encapsulated with Pluronic F-127 forming nanoparticles (NPs). Upon perhydrolysis reaction with hydrogen peroxide - the most stable and abundant form of ROS, oxidation of the FOC results in degradation of the hydrophobic matrix of the NPs, giving rise to the chemiluminescence (CL) emission, the release of fluorinated alcohol acting as 19F MRI contrasting agent and drug release, at the same time. Thus, the ROS-sensitive nanoprobe may enable precise tracking of the inflamed tissues (cells undergoing excessive oxidative stress) via multiple imaging modalities accompanied with biomarker-specific drug delivery
Keywords: type of access: open access; Reactive oxygen species; peroxyoxalate chemiluminescence; 19F NMR/MRI; drug delivery; bioimaging; theranostics